A LBV perspective on political risk management in a multinational bank during the First World War. Issue 1 (18th April 2016) - Smith, Andrew
Abstract : Purpose: This paper aims to apply the Legitimacy-Based View (LBV) of political risk to the experience of the Hongkong and Shanghai Banking Corporation (HSBC) in the First World War. The paper shows that HSBC's ability to survive this conflict was due, in part, to its ability to manage political risk by maintaining legitimacy in the eyes of stakeholders in its home market(s), Hong Kong and the UK. Design/methodology/approach: This case study is based on the surviving internal correspondence from this period in the HSBC Group archives in London and other primary sources. Findings: This paper suggests that maintaining legitimacy in the home market is crucial to firm survival and profitability. Managers' efforts to bolster firm legitimacy should ensure that individuals in all of the relevant government departments continue to regard the multinational enterprise (MNE) as legitimate. Research limitations/implications: This paper shows that the LBV is a potentially powerful analytical tool, but it also argues that the LBV must be modified so as to incorporate insights from the theoretical literature on ethnic and national identities, particularly the insight that such identities are culturally constructed and malleable. Practical implications: Warfare tends to increase the degree to which a MNE's stakeholders feel emotional bonds to their respective nations. HSBC's experience in the First World War suggests that continued profitability in wartime may depend on the firm's ability to shed its peacetime "world citizen" identity in favour of one that is more closely aligned with that of its home nation. Preserving political capital in wartime may require the ruthless termination of relationships with clients and employees who are associated with the enemy nation. Another lesson that MNE managers can derive from this paper is that preserving legitimacy in the home country may require the head office to exert more control over overseas managers, than would be the case in peace. A MNE in wartime that is concerned about the loss of legitimacy in the home country should consider adopting an organizational architecture that temporarily reduces subsidiary autonomy. Originality/value: Buckley (2009) called for the re-integration of business history in International Business research. This paper is part of the ongoing historic turn in International Business and other management disciplines. This paper also argues that International Business scholars need to consider the impact of past wars on contemporary multinationals as we may witness the re-emergence of Great Power rivalries similar to those that led to the First World War. This paper proceeds on the assumption the probabilities of a war between two major capitalist economies are non-trivial and that additional investigation of the impact of major interstate warfare on MNEs is therefore merited. Historical research can help us to think about what a war between capitalist countries would mean for today's MNEs.